2014
DOI: 10.1007/s12603-014-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

An overview of structure, mechanical properties, and treatment for age-related tendinopathy

Abstract: Tendons transfer tensile loads from muscle to bone, which enable joint motions and stabilize joints. Tendons sustain large mechanical loads in vivo and as a result, tendons were frequently injured. Aging has been confirmed as a predisposing factor of tendinopathy and bad recovery quality following tendon repair. Current treatment methods are generally not effective and involve either symptomatic relief with non-steroidal antiinflammatory drugs and physical therapy or surgery when conservative treatments failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 75 publications
1
39
0
Order By: Relevance
“…One theory attributes the effect to the accumulation of chronic repetitive damage over time [ 23 ]. Another hypothesis is that age-related changes in tendon structure and biomechanics could decrease the loading capacity and regenerative capacity of the tendons [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…One theory attributes the effect to the accumulation of chronic repetitive damage over time [ 23 ]. Another hypothesis is that age-related changes in tendon structure and biomechanics could decrease the loading capacity and regenerative capacity of the tendons [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hallmarks of tendinopathies include COL1A1, COL1A2, COL4A1 and COL4A2 overexpression, fibril disorganization, increased collagen crosslinking, reduced tissue inhibition of MMPs (i.e. TIMP activity), and elevated expression of MMP2, MMP14 and MMP19 as well as of versican, biglycan and Dcn (Jelinsky et al, 2011;Parkinson et al, 2011;Dunkman et al, 2013;Zhou et al, 2014). Recent studies have also identified COL6A1/2/3 and COL12A1 as genes underlying one form of human 'myotendinopathy', which affects both myomatrix structure and tendon matrix structure (Bönnemann, 2011;Pan et al, 2013).…”
Section: Box 1 Tendinopathiesmentioning
confidence: 99%
“…Ageing is associated with an increasing incidence of tendinopathies and impaired tendon repair following injury [ 1 3 ]. These events are thought to result from age-related modifications in tendon structure, especially extracellular matrix (ECM) content, accumulation of mechanically induced micro-trauma and decreased regenerative potential of tendon tissue [ 1 , 4 7 ]. Tendon adaptability to loading conditions and its healing capacity depend predominantly on the cellular component, represented by tenocytes and tendon-derived stem cells (TDSCs) [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%